2012
DOI: 10.1002/smll.201101456
|View full text |Cite
|
Sign up to set email alerts
|

Structuration and Integration of Magnetic Nanoparticles on Surfaces and Devices

Abstract: Different experimental approaches used for structuration of magnetic nanoparticles on surfaces are reviewed. Nanoparticles tend to organize on surfaces through self-assembly mechanisms controlled by non-covalent interactions which are modulated by their shape, size and morphology as well as by other external parameters such as the nature of the solvent or the capping layer. Further control on the structuration can be achieved by the use of external magnetic fields or other structuring techniques, mainly lithog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 188 publications
(267 reference statements)
0
32
0
Order By: Relevance
“…In this context, it is very important to rationalize the study of exchange bias in FiM/AFM core–shell nanoparticles by addressing their spatial arrangement in well‐structured assemblies. An efficient approach to achieve this goal is to chemically assist the assembly of nanoparticles onto substrates in order to tune the interparticle distance and the dimensionality of the assemblies. Until now, the collective properties of FiM/AFM core–shell nanoparticles have been very scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is very important to rationalize the study of exchange bias in FiM/AFM core–shell nanoparticles by addressing their spatial arrangement in well‐structured assemblies. An efficient approach to achieve this goal is to chemically assist the assembly of nanoparticles onto substrates in order to tune the interparticle distance and the dimensionality of the assemblies. Until now, the collective properties of FiM/AFM core–shell nanoparticles have been very scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…154 This has proven to be an extremely useful tool for nanofabrication, with an extensive body of research investigating the various methods and applications of self-assembly. 154,155,156 Combining multiple methods of self-assembly has even succeeded in the creation of an operational 3D motor from a single polymer crystal. 157 Successive self-assembly processes allowed a crystal of R-hydroxyl-ω-thiolterminated polycaprolactone to be coated in three different types of nanoparticles: gold nanoparticles to facilitate optical visualisation; platinum nanoparticles to drive the motor by catalysing the decomposition of the surrounding hydrogen peroxide solution; and iron oxide nanoparticles to allow for remote magnetic guidance of the motor.…”
Section: Self-assemblymentioning
confidence: 99%
“…magnetic field, electric field, pressure gradient, light and laser) [46,47]. Magnetic field directed self-assembly (MDSA), a recently emerged external self-assembly approach, has been more introduced as a powerful strategy for controlling the structure and properties of nanostructures and showed an excellent prospect for the fabrication of modified electrodes [48][49][50]. In our previous M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 studies, MDSA has been confirmed as an efficient, convenient and timesaving approach to construct the orderly and oriented geometric nanostructure, which enhanced charge transfer capability and showed desirable electrochemical properties [51,52].…”
Section: Introductionmentioning
confidence: 99%